A rare case on ovarian hyperstimulation syndrome in a spontaneous singleton pregnancy - ., Neha; Chauhan, Madhubala; Chaudhary, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Spontaneous form of ovarian hyperstimulation syndrome in pregnancy (OHSS) is extremely rare and characterized by gastro-intestinal symptoms and complication of shift of fluid in the third space. It is often associated with multiple gestations, hypothyroidism, polycystic ovarian syndrome and molar pregnancy. Treatment depends on the patient’s clinical condition. The aim of this case report is to bring into light a case of spontaneous OHSS in a healthy Indian pregnant woman that presented with pain abdomen, abdominal distension and vomiting at 14 weeks of gestation without any of the above-mentioned risk factors. Ultrasonography showed a single viable intrauterine pregnancy along with bilateral enlarged cystic ovaries, ascites and raised CA-125 levels. There was no history of ovulation induction in present and previous pregnancy. We successfully managed the patient conservatively with Dopamine agonist Cabergoline and she delivered a healthy baby at 33 weeks. Although spontaneous OHSS is a rare entity, it should be included in differential diagnosis of acute abdomen in pregnant women. OHSS can lead to life threatening complications, early diagnosis is required for proper management.